Assessment of the social capital impact on the household income of the Russian Federation regions - N. Е. Karmanova; A. V. Koritskiy (Статистика и экономика)
Purpose of research. To identify the impact of social capital on economic development and income, using mathematical modeling. Also, based on the analysis of modern domestic and foreign literature on the theoretical foundations of social capital, to give a qualitative and quantitative characteristic of such indicators of social capital as marriage, divorce, the ratio of these indicators and the mechanisms of its possible impact on the income of Russian citizens.  Materials and methods. General scientific methods such as analysis and synthesis, induction and deduction, empirical methods were used to obtain scientific results. The theoretical basis of the study is the fundamental theoretical work and publications of Russian and foreign scientists in the field of social capital research as a factor affecting the development of the national economy as a whole and the income of the Russian population, in particular. The authors propose a methodological approach that distinguishes the study from other economists – this is mathematical modeling using the extended Cobb-Douglas production function with the inclusion of indicators representing human and social capital in the number of independent variables of this function. The variable, characterizing social capital is a statistical indicator “the ratio of marriage and divorce”, as a characteristic of the state of social (or its components of moral capital) in Russia. The calculations used data from statistical reference books “Regions of Russia. Socio-Economic Indicators”, “weighted” regressions, the indicator “number of people employed in the region’s economy” was used as a weighted variable.  Results. Calculations of spatial regression equations, using official statistics are carried out. The statistical evaluation of the effect of social capital on the income differentiation of the population in the regions of Russia is presented. Social capital, as shown by the calculations of the regression equations, along with the fixed capital per worker and the average level of education of the population, employed in the economy of the regions, has a significant impact  on both income and differentiation of income of the population of Russian regions. In addition, calculations indicate that the frequency of divorces adversely affects the income of the employed population of the regions of Russia.  Conclusion. Calculations and analysis of statistical indicators show that social capital in Russia does not accumulate, but degrades. This can lead to undesirable consequences in terms of economic development, preventing the movement along progressive trajectories. In particular, for example, to the spread of such a negative phenomenon as information asymmetry in different groups: at work or in the family, which can interfere with productive work and result in lower quality of work, service, efficiency and competitiveness. Therefore, there is an urgent need to envisage a number of measures to accumulate and save social capital. Including the strengthening of the family, which makes a significant contribution to the creative processes of trust, and accordingly, the growth of social capital.